Intelligence Quotient (IQ) as a Predictor of Reading Comprehension and Writing Achievement of EFL Learners - Ningrum, Ary Setya B.; Wibowo , Rohmat Agung (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2017)
This study aimed at investigating Intelligent Quotient (IQ) as a predictor of reading comprehension and writing achievement as well as to correlate the students' reading comprehension with their writing achievement. The participant of the study were 32 senior high school Indonesian students. There are three instruments used in this study, those are IQ test, reading comprehension test, and writing test. Upon obtaining the whole data needed, Pearson Product Moment formula was employed to determine the correlation of IQ with reading comprehension and writing achievement as well as reading comprehension with writing achievement. The result of this study revealed that IQ made significant contribution in predicting reading comprehension (23.42%) and writing achievement (16.08%). In addition, the correlation coefficient of reading comprehension and writing achievement shows that they are moderately correlated (r=.587), meaning that reading comprehension contributes as many as 34.45% to writing achievement.